2021
DOI: 10.3390/ph14060533
|View full text |Cite
|
Sign up to set email alerts
|

The Beta-Lactam Resistome Expressed by Aerobic and Anaerobic Bacteria Isolated from Human Feces of Healthy Donors

Abstract: Antibiotic resistance is a major health problem worldwide, causing more deaths than diabetes and cancer. The dissemination of vertical and horizontal antibiotic resistance genes has been conducted for a selection of pan-resistant bacteria. Here, we test if the aerobic and anaerobic bacteria from human feces samples in health conditions are carriers of beta-lactamases genes. The samples were cultured in a brain–heart infusion medium and subcultured in blood agar in aerobic and anaerobic conditions for 24 h at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…According to the CARD prevalence 3.0.9 update, there is wide variability in ARG phenotypes between commensals from the same and different genera. 39 These data, in combination with the results from this study and others assessing antimicrobial susceptibility in bacteria often considered off-target, 61 , 62 provide further evidence that intra- and inter-species variation is important to consider.…”
Section: Discussionsupporting
confidence: 69%
“…According to the CARD prevalence 3.0.9 update, there is wide variability in ARG phenotypes between commensals from the same and different genera. 39 These data, in combination with the results from this study and others assessing antimicrobial susceptibility in bacteria often considered off-target, 61 , 62 provide further evidence that intra- and inter-species variation is important to consider.…”
Section: Discussionsupporting
confidence: 69%
“…Aeromonas species are generally resistant to betalactams (blaCMY), and this was also observed in this study. The presence of blaCMY and ampH genes in all isolated A. rivipollensis was not a surprise, as they have been recorded in several bacteria isolates including Aeromonas species [59,60]. In addition, the genome of isolate G87 was only one of the sequenced A. rivipollensis in this study that showed a multidrug tetracycline-resistance gene.…”
Section: Discussionsupporting
confidence: 54%
“…prausnitzii genogroups might contain class A BL [ 105 ], which was also the dominant BL class in the shotgun validation group, while Bacteroides sp. is a well-known group of BL-producing bacteria [ 106 , 107 ]. In addition, cbl A gene of class A BL with an annotated taxonomic source of B .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that some F. prausnitzii genogroups might contain class A BL [105], which was also the dominant BL class in the shotgun validation group, while Bacteroides sp. is a well-known group of BL-producing bacteria [106,107]. In addition, cbl A gene of class A BL with an annotated taxonomic source of B. uniformis was the predominant BL gene in the shotgun validation group, and its abundance was higher in the post-eradication group.…”
Section: Plos Onementioning
confidence: 99%